2005
DOI: 10.1021/ic048819r
|View full text |Cite
|
Sign up to set email alerts
|

Nanophase Iron Phosphate, Iron Arsenate, Iron Vanadate, and Iron Molybdate Minerals Synthesized within the Protein Cage of Ferritin

Abstract: Nanoparticles of iron phosphate, iron arsenate, iron molybdate, and iron vanadate were synthesized within the 8 nm interior of ferritin. The synthesis involved reacting Fe(II) with ferritin in a buffered solution at pH 7.4 in the presence of phosphate, arsenate, vanadate, or molybdate. O2 was used as the oxidant to deposit the Fe(III) mineral inside ferritin. The rate of iron incorporation into ferritin was stimulated when oxo-anions were present. The simultaneous deposition of both iron and the oxo-anion was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 51 publications
3
73
0
Order By: Relevance
“…The addition of 1.0, 2.5, 5, and 10 mM phosphate to this reaction caused an increase in the initial rate of apo transferrin loading, indicating that the phosphate stimulates the rate of Fe 2? oxidation at the H ferritin ferroxidase center as previously reported (Orino et al 2002;Aitken-Rogers et al 2004;Cheng and Chasteen 1991;Polanams et al 2005). However, above 2.5 mM phosphate, the final absorbance begins to decrease, indicating that at these higher phosphate concentrations, the formation of the Fe(III)-phosphate complex begins to compete with H ferritin for the added Fe 2?…”
Section: Recombinant H and L Ferritinssupporting
confidence: 75%
See 2 more Smart Citations
“…The addition of 1.0, 2.5, 5, and 10 mM phosphate to this reaction caused an increase in the initial rate of apo transferrin loading, indicating that the phosphate stimulates the rate of Fe 2? oxidation at the H ferritin ferroxidase center as previously reported (Orino et al 2002;Aitken-Rogers et al 2004;Cheng and Chasteen 1991;Polanams et al 2005). However, above 2.5 mM phosphate, the final absorbance begins to decrease, indicating that at these higher phosphate concentrations, the formation of the Fe(III)-phosphate complex begins to compete with H ferritin for the added Fe 2?…”
Section: Recombinant H and L Ferritinssupporting
confidence: 75%
“…As indicated above, CKD patients have elevated serum ferritin concentrations suggesting a possible role for ferritin as an NTBI binding protein. Also, consistent with this hypothesis are reports that ferritin has increased rates of iron loading in the presence of phosphate (Aitken-Rogers et al 2004;Orino et al 2002;Cheng and Chasteen 1991;Polanams et al 2005;de Silva et al 1993).…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…In vivo the phosphate contents of ferritin iron cores appear to be in dynamic equilibrium with cell phosphate (Ford et al, 1984) and it has long been suggested that phosphate plays a role in iron home-ostasis (Powell, 1998). This assumption has recently been supported by the fact that phosphate can stimulate the rate of iron uptake by providing binding sites on the mineral surface for incoming iron atoms and as such may play a role in the oxidation of Fe 2+ on the mineral surface (Polanams et al, 2005).…”
Section: +mentioning
confidence: 96%
“…A synthesis of ferrimagnetic ferritin (γ-Fe 2 O 3 ) was achieved by a chemical remineralization procedure [7,8] with the assistance of H 2 O 2 oxidant in 3-[(1,1-dimethyl-2-hydroxyethyl)amino]-2-hydroxypropanesulfonic acid(AMPSO) buffer (pH 8.5) at 65 o C under N 2 gas. Biomineralization of other metals (i.e., Co [9,11], Mn [12][13][14], Ni [15], and Pd [16]), semiconductors (CdS) [17], and metal-oxo-anions composites [18] into the ferritin cavity has also been reported. Wong et al demonstrated the magnetic transition from superparamagnetic to ferromagnetic CoPt cored ferritin [19][20].…”
Section: Introductionmentioning
confidence: 99%